Synthesis and characterization of a novel hydroxypropyl chitosan-graft-β-Cyclodextrin copolymer as potential drug carrier. Issue 5 (24th July 2019) - Xie, Jun; Qin, Dawei; Han, Yanhong; Wang, Lizhen
Abstract: One of the most attractive fields in drug delivery is the design of nanoparticles that could be used to transport drugs into the target place at appropriate time. This paper describes the preparation of a novel hydroxypropyl chitosan-graft-β-cyclodextrin (HPCS-g-β-CD) copolymer using the 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N -hydroxysuccinimide (NHS) promoted condensation reaction. Structural characterization was finished with FTIR and 1 H NMR spectra, which confirmed the grafting of β-cyclodextrin (β-CD) onto hydroxypropyl chitosan (HPCS). The thermal properties were studied based on DSC and TGA analyses, which revealed the fact that grafting of β-CD onto HPCS resulted in obvious enhancement of the decomposition temperature of the copolymer. Aqueous solution of HPCS-g-β-CD copolymer was stable at pH 7-8 based on the Zeta potential test. The morphological characteristics were investigated by SEM, TEM and AFM analysis, and the results indicated that this copolymer had three-dimensional structure which was suitable for loading drugs. Graphical Abstract: